Effect of High Protein Diet in Activity of Antioxidants and Level of Inflammation on Sprint Athlete - Endang Sri Wahjuni; Soetanto Hartono (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
This study aims to analyze the effect of a low-carbohydrate high-protein diet to increase the level of antioxidant, decrease inflammation and improve performance of athlete. The research was carried out by experimental research methods, within the design of "Randomized Control Group Pretest Posttest Design". A sample was taken from 20 people who met the inclusion and exclusion criteria from 30 teenage athletes in PASI East Java sprints. The Data were collected by measuring the sprint results by finish photo camera and laboratory examinations to determine the levels of antioxidants (SOD) and the inflammation degree (TNF α) in blood. The data were analyzed using multivariate technique (Manova) Hotelling's method (T2). Hypothesis testing using α 0.05. The results and conclusions of the study stated that the normal diet had no effect on the variables of sprint running speed, SOD and TNF-α levels. While low-carbohydrate and high-protein diet can increase SOD levels of 211.44 /gHb, reduce (TNF α) at least 0.309 pg/ml, and the average increase in antioxidant activity caused by low-carbohydrate-high-protein diet is 24,989 / gHb higher than normal diet, the decrease in the degree of inflammation is 0.196 pg/ml, however, it has no effect on the speed of sprint.